A characterisation of passive and active interactions and their influence on students' achievement using Moodle LMS logs. (1st January 2011) - Pascual-Miguel, Félix; Chaparro-Peláez, Julián; Hernández-García, Ángel; Iglesias-Pradas, Santiago
During the last years, there has been much concern about learning management systems' (LMS) effectiveness when compared to traditional learning and about how to assess students' participation during the course. The tracking and monitoring capabilities of most recent LMS have made it possible to analyse every interaction in the system. The issues addressed on this study are: To answer these questions, a set of interaction types from Moodle LMS activity record logs has been analysed during two years in online and in-class Master's degrees at the UPM. The results show partial or no evidence of influence between interaction indicators and academic performance, although the proposed categorisation may help detect learning witnesses.